Escala de comportamentos de dirigir sob influência de álcool : elaboração e evidências psicométricas - Silva, Phillip Dyamond Gomes da (2022)
Reports about traffic accidents are recurrent in Brazilian daily life. The theme has gained space and popular appeal given the alarming numbers of people directly and indirectly affected by this problem, with driving under the influence of alcohol as one of the main risk factors. Despite the numerous measures taken by municipal, state, federal governments and international bodies in order to alleviate/eradicate traffic accidents resulting from driving under the influence of alcohol, mortality rates related to this factor have remained stable in recent years, alerting to the need to develop new measures that deal with the issue not only analyzing variables external to the individual, but taking into account the human and individual factor of people, which precedes their particular choices: their personality traits. Since Brazil does not have an effective measure that takes this variable into account and correlates it with the risk factor mentioned, the present research aimed to develop and test the structural validity of the Scale of Driving Behaviors Under the Influence of Alcohol. (ECDIA), a measure to quantify the history of driving under the influence of alcohol, and once quantified, to correlate this history with personality traits in order to verify if these can predict the behavior of drunk driving. For this, a Principal Component Analysis was carried out with a sample of 301 participants, mostly married (53.7%), female (52.2%) and aged between 18 and 77 years (M = 35, 4; SD = 11.96). The results indicated that the ECDIA proved to be a viable tool for measuring the history of drinking and driving behavior. Regarding correlations, it was found that people with higher scores in obscure personality traits such as Machiavellianism, Psychopathy, Narcissism and traits such as Sensation Seeking, Neuroticism and Extraversion tend to express drinking and driving behavior more frequently. In addition, the variables with the highest degree of prediction for drunk driving behavior were Risky Driving, Alcohol Consumption and Aggressive Driving. Therefore, it is possible to conclude that the ECDIA has presented itself as a satisfactory model for measuring the history of drinking and driving and that such behavior can be partially explained by some personality traits.